2001
DOI: 10.1007/s001250051665
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent and independent vasodilation studied at normoglycaemia in Type I diabetes mellitus with and without microalbuminuria

Abstract: Aims/hypothesis. We examined whether endothelial function is impaired in patients with Type I (insulindependent) diabetes mellitus under conditions of near-normoglycaemia compared with age-matched healthy control subjects. Our aim was to determine whether microalbuminuria is associated with endothelial dysfunction in Type I diabetes. Methods. Endothelial function, measured as postischaemic flow-mediated dilatation of the brachial artery using ultrasound, was compared among 17 microalbuminuric and 17 normoalbum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 34 publications
(43 reference statements)
9
93
0
6
Order By: Relevance
“…The slightly more pronounced impairment of glomerular hemodynamics in type 2 diabetic patients with microangiopathy may suggest that the defect of NO regulation of glomerular function worsens progressively with the occurrence of renal complications. These findings are in keeping with the observations of Dogra et al (38) who have shown that endothelial dysfunction is present in normoalbuminuric type 1 diabetic patients, and is more marked in microalbuminurics.…”
Section: Discussionsupporting
confidence: 93%
“…The slightly more pronounced impairment of glomerular hemodynamics in type 2 diabetic patients with microangiopathy may suggest that the defect of NO regulation of glomerular function worsens progressively with the occurrence of renal complications. These findings are in keeping with the observations of Dogra et al (38) who have shown that endothelial dysfunction is present in normoalbuminuric type 1 diabetic patients, and is more marked in microalbuminurics.…”
Section: Discussionsupporting
confidence: 93%
“…36 The finding of an inverse association between UACR and NMD indicates that increased urinary albumin excretion in hypertensive subjects may be a marker of arterial smooth muscle hyporeactivity to exogenous sources of NO. Several previous studies 27,28,31,37 have reported significantly lower NMD in microalbuminuric than in normoalbuminuric patients; however, the subjects in these studies were mostly normotensive diabetics and non-diabetics. Vasodilatation owing to nitroglycerin involves Abbreviations: BMI, body mass index; DBP, diastolic blood pressure; FMD, flow-mediated dilatation; HDL, high-density lipoprotein; SBP, systolic blood pressure; UACR, urinary albumin/creatinine ratio.…”
Section: Discussionmentioning
confidence: 82%
“…As FMD primarily results from the endothelial release of nitric oxide (NO), 26 the inverse association between UACR and FMD indicates that increased urinary albumin excretion in hypertensive individuals may be a manifestation of systemic endothelial dysfunction. Previous studies investigating the relationship between urinary albumin excretion and FMD have yielded conflicting results, with some showing a significant association [27][28][29][30][31] and others showing no such association. [32][33][34] The reasons for these divergent observations are not clear, although methodological differences between various studies could contribute.…”
Section: Discussionmentioning
confidence: 97%
“…Brachial artery ultrasonography was carried out [28]. Briefly, a 12-megahertz transducer connected to an Acuson Aspen ultrasound (Acuson, Mountain View, Calif, USA) and fixed in position by a stereotactic clamp 5 to 10 cm proximal to the ante-cubital crease was used to image the brachial artery.…”
Section: Methodsmentioning
confidence: 99%